Guanxi Networking, Associational Involvement, and Political Trust in Contemporary China. Issue 125 (2nd September 2020) - Chen, Yunsong; He, Guangye; Li, Shuanglong
ABSTRACT: Much scholarly attention has been devoted to the subject of whether and how social connections affect political trust. China provides a critical case because of the unique guanxi networks and the symbiosis between the state and non-governmental associations. In the Chinese context, this analysis proposes that: 1) informal social ties impair political trust since guanxi networking offers provisional publics the transmission of political stimuli, 2) formal social ties foster political trust because associations and the state coexist in a state-dominant symbiotic sphere that brings about political trust assimilations by helping associations realize their agendas and interests. Based on survey data from urban China, findings from both standard models and auxiliary instrumental variable analyses generally support these predictions.